Comparative motives of Ismail Kadare's work - Kamberi, Kamber (Technium Social Sciences Journal, 2022)
Ismail Kadare, the most famous writer of today's Albanian literature, is also one of the most famous writers of contemporary literature in general. Therefore, whenever we mention this genius of Albanian belles-letters, first of all our mind goes to his work, its structure, themes, characters, actions and events, words and messages, and of course, the artistic features. Although it is rare to come across in the works of any other author a literary approach that can be compared to the singularity of this author, the meeting points and messages are evident. The artistic singularity is easily discernible, but the more one delves into his creative gallery, the more inevitable it is to enter into the many realms of the imagination to finally come to the conclusion that the upper realms are possessed only by geniuses, just like the sovereign of Albanian letters. The intertwining of the whole corpus of his works, with the way of narration and action, give interesting mosaics that together build the great monumental picture, which can be designed and realized only by the imagination of a writer of a promimence like him. Another motivation to deepen the gaze appears when comparisons are made with the works and characters of other authors of world literature. Comparable to meeting points in words and messages from genius motifs of different times. Geniuses break times.